Towards photosynthetic hydrogen production - Craig, Sean (2022)
The need to develop a sustainable energy is crucial and one of the foremost global challenges facing humanity, driven by a continuing global population expansion and anthropogenic climate change. Hydrogen (H2) is a clean burning fuel which, however production relies on fossil fuels that is both unsustainable and environmentally unfriendly. The current global market is currently estimated at $115.25 Billion and expected to rise to $154.74 Billion by 2022.